Kindler syndrome: A rare case report - Shweta Satyanarayan Kandikatla; Shylaja Someshwar; Pranjal Ahire (Wolters Kluwer Medknow Publications, 2021)
Kindler syndrome is a very rare genodermatosis with an autosomal recessive pattern and about 250 cases have been reported worldwide. The mutant gene is Fermitin family homolog 1 gene (KIND1), located on chromosome 20p12.3, which encodes for focal adhesion protein "Fermitin family homologue 1 protein" or Kindlin-1. It is characterized clinically by acral blistering in infancy, photosensitivity improving with age, progressive poikiloderma, cutaneous atrophy, dental problems, and various forms of mucosal involvement. Histologically, it is characterized by flattened and atrophic epidermis, edematous dermoepidermal junction, vacuolar degeneration of basal cells, pigmentary incontinence, and sparse perivascular lymphocytic infiltrate. Here, we report a case with classic skin manifestations in a 13-year-old female without photosensitivity.